Determination of rainfall attenuation at millimeter wave band for the design of 5g and higher bandwidth radio equipment for terrestrial paths in the tropical region (2020)
Millimeter Wave (mmW) radio systems operating at 30 to 300GHz band provides higher bandwidth, frequency reuse and communications security. With the available wide bandwidth, millimeter wave equipment is capable of achieving 10 Gbps full duplex capacities. The mean annual 1-minute RR (mm/hr) ranged from 87.25 in the coastal region to 51.0mm/hr in semi-arid region. The ITU-R predicted RR ranged from 109.10mm/hr in the coast to 91.90mm/hr in the semi-arid region. The ITU-R overestimated the rain rate by 23.83% in the semi-arid region while at the coastal region, it was over-estimated by 12.47%. The highest value of specific attenuation (R g) at horizontal polarization (Hp) and vertical polarization (Vp) for the two regions occurred at 120 and 150GHz MWFs and R P g H > R P g V. The clear signal band at 20km Path length were estimated to be 40 and 45GHz across the regions, while the predicted value by ITU-R is also 40GHz. However, the ITU-R over predicted the value of attenuation at this frequency band by 13.16% and 35.29% at the coastal and semi-arid locations respectively. included 150GHz which overlaps with 45GHz band. The path attenuation across the regions at 40GHZ ranged from 112.58dB to 164.14dB while at 45GHZ, it ranged from 122.02dB to 175.57.45dB. The range of the ITU predicted value of path attenuation at 40GHz and 45GHz were 170.20dB to 192.18dB and 181.83 dB to 204.43dB respectively.